O panorama das políticas públicas federais brasileiras voltadas para as empresas de pequeno porte - Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– The current study consists in an analysis of the set of federal public policies of the Brazilian government aimed at the segment of micro, small and medium enterprises. It is not an evaluation of their impacts, but only a mapping of existent policies and a first analysis of their coverage. This set of policies was divided in four groups. The juridical order, in which the main legal and regulatory instruments that favor small businesses. The institutional structure, in which the governmental apparatus directed specifically at this segment is described. The governmental plans and policies, in which the form of insertion and the treatment given to these firms in the many government plans are explained. And finally, the specific programs and actions, encompassing the diverse instruments that aim to stimulate the segment. The primary conclusion of the study is that there is an abundance of mechanisms in the country regarding the support of small sized businesses, although there is a lack of focus and coordination between them and between the responsible agencies, which turns out to negative impact in their efficacy.
Keywords: N8; H25; O2; 330; small business; development policies